Tunable and high-performance self-powered ultraviolet detectors using leaf-like nanostructural arrays in ternary tin zinc sulfide system. (October 2021) - Ebrahimi, Sema; Yarmand, Benyamin
Abstract: Recently, self-powered ultraviolet (UV) detectors have received increasing attention for developing the future demands for optoelectronic devices due to their distinguished photoresponse properties. In this study, an emerging type of self-powered UV detectors using the ternary Snx Zn1-x S alloy thin films (0.20 ≤ x ≤ 0.40 mol) were fabricated using the solvothermal process. The structural study showed the formation of two distinct phases of ZnS and SnS for the samples with high content Sn 2+ ions. According to the ideal crystal-growth mechanism proposed by periodic bond chain theory, a morphological evolution from nanorods to nanoflakes and unique aligned three-dimensional leaf-like nanostructures was achieved by enhancing the Sn 2+ content up to the maximum value of 0.40 mol. The optical properties featured the less influence of band tailing on the band gap energy at the high concentration of Sn 2+ ions, resulting in the widening of the band gap energy up to 4.56 eV thanks to the Burstein-Moss effect. From the photosensing measurements, the Schottky barrier heights of the devices were found to significantly reduce under UVB exposure as the Sn 2+ content increases, confirming a high Ion /Ioff ratio (>10 3 ) for the devices. The UV detectors exhibited superior self-powered characteristics under UVB illumination, having high photosensitivity and fast photoswitching response times (τr = 1.9 and τd = 2.6 ms) at zero voltage. Interestingly, the photoresponse performance of UV detectors can be adjusted by varying the content of Sn 2+ ions, which signifies that tunable self-powered UV detectors can be designed by varying the Sn 2+ concentration in the ternary Snx Zn1-x S system. Graphical abstract: Image 1 Highlights: UV detectors based on Snx Zn1-x S thin films were fabricated by solvothermal method. 3D leaf-like nanostructures were obtained at high content of Sn 2+ . Open-circuit voltage was enhanced exponentially by increasing the Sn 2+ content. UV detectors exhibited superior performance at the self-powered mode.